Antioxidant activity of Clematis brachiata Thunb. leaf (Bangladesh Journal of Scientific and Industrial Research, 2018)
The antioxidant activity, total phenolic and flavonoid contents of different extracts of the Clematis brachiata Thunb leaves were determined. The antioxidant activity was evaluated using spectroscopic methods against 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) and 2,2′-azinobis [3-ethylbenzothiazoline-6-sulphonic acid] diammonium salt radical cation (ABTS). Folin Ciocalteu method was used to determine the total phenolics and Aluminium Chloride Colorimetric method was used to determine the flavonoids contents in these extracts. The results showed that the methanol extract of the leaf exhibited the highest antioxidant activity with the value of 180.45 ±2.4 μg mL-1 in DPPH and 60 ±0.80 μg mL-1 in ABTS assay among the extracts. The methanol extract contains more phenolic compounds (178±2.20 mg/g as galic acid equivalent per g dry matter) and the acetone extract contains more flavonoids (135.11±1.20 mg/g as quercitin equivalent per g dry matter) among the extracts. This study provides the evidence that the leaves of the Clematis brachiata Thunb could be a good source of natural antioxidant.Bangladesh J. Sci. Ind. Res.53(3), 185-192, 2018